Հրաչյա Հովհաննիսյանի աշխարհընկալման յուրահատկությունները - Տաթևիկ Պողոսյան (ՀՀ ԳԱԱ հրատ.)
В статье раскрываются особенности мировосприятия Грачья Оганисяна, в основе которого лежат любовь и вера в человека. В частности,указывается, что для него поэзия одна из наилучших средств для увеличения любви и веры в мире. In this article Tatevik Poghosyan attempts to reveal Hrachya Hovhannisyan’s worldview, showing that it is based on love and faith in human beings. Particularly, it points out that, to him, poetry is one of the best ways to increase love, faith and humanism.
Keywords: Literature; Criticism